2018
DOI: 10.1007/s10792-018-0918-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness following trabeculectomy and its correlation with the decline in intraocular pressure

Abstract: Choroidal thickness appears to increase temporarily after trabeculectomy and these changes were not correlated with the decline in intraocular pressure. Further research is required to fully understand this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In accordance with previous studies performed on trabeculectomy, we found a significant increase in CT both in macula and in peripapillary region after the decline of the IOP, already 24 h after surgery [3,[7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies performed on trabeculectomy, we found a significant increase in CT both in macula and in peripapillary region after the decline of the IOP, already 24 h after surgery [3,[7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, SFCT tends to be negatively correlated to IOP [ 33 , 34 , 35 , 36 , 37 , 38 ]. As both IOP and SFCT decrease in our study, IOP variation does not explain the SFCT decreases.…”
Section: Discussionmentioning
confidence: 99%